High photocurrent in oligo-thienylenevinylene-based small molecule solar cells with 4.9% solar-to-electrical energy conversion1. Issue 21 (7th June 2015) - Montcada, Núria F.; Domínguez, Rocío; Pelado, Beatriz; Cruz, Pilar de la; Palomares, Emilio; Langa, Fernando
<x xml:space="preserve">Abstract</x> A set of five novel oligo-thienylenevinylene organic molecules have been synthesized and characterized for use as electron donor moieties in bulk-heterojunction solution-processed organic solar cells combined with PC71BM as an electron acceptor.